2021
DOI: 10.1108/ijem-07-2020-0345
|View full text |Cite
|
Sign up to set email alerts
|

The utilization of Internet marketing communication tools by higher education institutions (on the example of Poland and Ukraine)

Abstract: PurposeThe purpose of this study is to compare and contrast Internet marketing communication tools used to accomplish key marketing goals between European Union higher education institutions (HEIs) and non-EU HEIs, such as in the case of Poland and Ukraine.Design/methodology/approachIn the article, the authors used the literature review method to justify the importance of implementing HEI marketing strategy based on marketing communications with Internet users, and thus to justify the relevance of the chosen r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 24 publications
0
9
0
7
Order By: Relevance
“…For instance, out of a sample of 13-17 year olds in the U.S., 95% of them endorsed owning a smartphone or accessing one, 97% of them claimed using one or more popular social media platforms (e.g., YouTube, Instagram), and 45% of them stated that they spend a vast majority of their daily time online (Anderson & Jiang, 2018). Although the current study participants ranked social media as a less influential approach, Kisiołek, et al (2021) found that social media and school websites were the two most effective online marketing promotion approaches for higher education. Therefore, to keep up with the trend, it is recommended that flight schools also utilize the social media approach to maximize recruitment efforts.…”
Section: Marketing Promotion Approachesmentioning
confidence: 54%
“…For instance, out of a sample of 13-17 year olds in the U.S., 95% of them endorsed owning a smartphone or accessing one, 97% of them claimed using one or more popular social media platforms (e.g., YouTube, Instagram), and 45% of them stated that they spend a vast majority of their daily time online (Anderson & Jiang, 2018). Although the current study participants ranked social media as a less influential approach, Kisiołek, et al (2021) found that social media and school websites were the two most effective online marketing promotion approaches for higher education. Therefore, to keep up with the trend, it is recommended that flight schools also utilize the social media approach to maximize recruitment efforts.…”
Section: Marketing Promotion Approachesmentioning
confidence: 54%
“…Today, we live in a dynamic, fast-paced world where everyone has a limited time pushing us to see the undeniable significance of social media channels and tools and their benefits to businesses and our lives [22,23]. When focusing on social media benefits in the higher educational sector in Lebanon, we can see that social media is limited to attracting prospects to the university and, unfortunately, lacks focus on the academic achievements of the university as research and academic centers.…”
Section: Discussionmentioning
confidence: 99%
“…Summarizing methodological and applied approaches to the analytics of HE efficiency developed in the works of Brint and Clotfelter [2], Matyukh [9], Moyseyenko [12], we propose to use three types of economic efficiency indicators: 1) result indicators that reflect the activity of the HEIs in absolute terms; 2) performance indicators that make it possible to compare absolute indicators per unit of HEIs assets, student, etc. ; 3) income diversification indicators that reflect the specific weight of income sources from various activities in total revenues of the HE system.…”
Section: Legal Framework International and National Educational Standardsmentioning
confidence: 99%